(untitled) (Global Journal of Science Frontier Research, 2021)
This work presents a new approach to gravitation. Instead of seeing mass as a source of gravitation, the opposite is assumed here. Namely, gravitation has been there first and ever since. Masses were brought into the game later, following highly energetic interactions between electromagnetic fields (photons), with the gravitation field. These interactions resulted in photon annihilation and pair (or jets) production processes. Though pair production is forbidden kinematically in an empty space, it is allowed when the interaction of an incoming photon with gravitation field occurs. Quantum fluctuations in the gravitation field create very intense geometrical distortions in spacetime which in turn allows for photons to undergo momentum changes in favor of pair production processes.